The forms of history in the nineteenth century: the regimes of autonomy in Brazilian historiography - Araujo, Valdei; Cezar, Temístocles (Historein, 2018)
The forms of history is not a neutral expression. It alludes to the more general questions about the forms that history can take, in disciplinary terms, to the content of its discourse, or to the design, structure and physical ontology of historical material (form before content). In other words, the forms of history lead the historian to self-reflection in relation to the modalities of the research (the institutional situation, concerns and methods), the writing and the dissemination of history. The connection between nation and the forms of history seems indisputable and indissoluble. Our proposal is to go beyond this axiomatic formulation. Therefore, we propose an inversion of its assumptions and ask when was a conception of history founded in Brazil and how history becomes a knowledge of itself, that is, a subjective category of awareness, to then become the depository of knowledge about the nation, its primordial or most visible object throughout the nineteenth century.